Identification of destabilizing residues in HLA class II-selected bacteriophage display libraries edited by HLA-DM - Raddrizzani, Laura; Kropshofer, Harald; Hämmerling, Günter J. (European journal of immunology, 2006)
HLA-DM (DM) functions as a peptide editor by catalyzing the release of class II-associated invariant chain peptides (CLIP) and other unstable peptides, thus supporting the formation of stable class II-peptide complexes for presentation. To investigate the general features that determine the DM susceptibility of HLA-DR1/peptide complexes, we generated a large DM-ensitive peptide repertoire from an M13 bacteriophage display library using a novel double selection protocol: we selected bacteriophage capable of binding to DR1 molecules and, subsequently, we enriched DR1-bound bacteriophage susceptible to elution by purified DM molecules. Sequence and mutational analyses of the DR1/DM double-selected peptides revealed that the amino acids Gly and Pro play a destabilizing role in the dissociation kinetics of DR1 ligands. This observation was confirmed also in natural peptide sequences such as CLIP 89 - 101, HA 307 - 319 and bovine collagen II (CII) 261-273. Our results demonstrate that DM susceptibility does not only depend on the number and nature of anchor residues, or the peptide length. Instead, less obvious sequence characteristics play a major role in the DM editing process and ultimately in the composition of peptide repertoires presented to T cells.
First published: 28 March 2006
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 16.02.2021